Hugging the trees: the story of the Chipko Movement - Weber, Thomas (New Delhi, 1987)
Chipko, loosely translated, means 'to hug'. And that is literally what members of the Chipko movement in the Himalayas do-they save trees marked for felling by hugging them. As with all mass movements, there are several factions within the Chipko movement but while the emphases of the various groups may vary slightly, they all work towards the prevention of tree felling and the longer term goal of reforestation and saving the environment. This book traces the development of the Chipko movement from its earliest days, looks at the contribution of women to the various programmes, examines the Gandhian ideas that the workers are pledged to implement, and profiles the leading lights of the movement-men like Sunderlal Bahuguna and Chandi Prasad Bhatt. Most important, the book reiterates the message that ours is a small world, where ecological disasters do not recognize national boundaries, and where the only way to prevent further damage is to work towards a permanent economy of man in nature.
Keywords: Forest protection